2017
DOI: 10.15225/pnn.2017.6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life in Patients After Surgical Treatment of a Lumbar Disc Herniation — a Preliminary Study

Abstract: Introduction. Herniated intervertebral disc is a disease that is one of the main causes of sciatica and severe, sharp back pain and usually concerns adults aged 35 to 50 years. Aim. To evaluate the effect of surgical treatment on the quality of life in patients hospitalized and subjected to surgery due to a disk herniation in the lumbar spine. Material and Methods. The study included 50 patients treated surgically for disc herniation in the lumbar region. The diagnostic survey method was applied for the purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The results showed that the mean level of pain intensity in patients seeking medical care due to chronic LBP was 6.75 on the VAS. Similar results were obtained by other authors who observed that before spine surgery there were various degrees of pain in all respondents; however, VAS score ranged between 6 and 8 was the most common .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that the mean level of pain intensity in patients seeking medical care due to chronic LBP was 6.75 on the VAS. Similar results were obtained by other authors who observed that before spine surgery there were various degrees of pain in all respondents; however, VAS score ranged between 6 and 8 was the most common .…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have shown that strong chronic LBP affects daily functioning and significantly lowers the QOL , which was confirmed in our own study. The results showed that people suffering from LBP rated the quality of their life the lowest in the physical domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies showed improvement in each component and overall quality of life. [18][19][20] Improvement in terms of mental as well as social wellbeing is seen as all of these factors are attributed to pain. 21 There is disease specific questionnaire for assessing outcomes for spinal disease.…”
Section: Discussionmentioning
confidence: 99%